1997
DOI: 10.1046/j.1365-2141.1997.4223235.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant FHIT transcripts in acute myeloid leukaemia

Abstract: Summary.Recently the FHIT gene (fragile histidine triad gene) has been identified at chromosome 3p14.2 and a high frequency of abnormalities in this gene has been demonstrated in various cancers. To determine the role of the FHIT gene in leukaemia, bone marrow or peripheral blood from 62 acute myeloid leukaemia patients and five haemopoietic cell lines (HL60, U937, Raji, KG-1, K562) were analysed by reverse transcription of the FHIT mRNA followed by PCR amplification and sequencing of the products. To detect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…Decreased or altered expression of the FHIT gene has been reported in fresh leukaemia samples and cell lines (Lin et al, 1997;Sugimoto et al, 1997), and loss of normal FHIT function is considered to be involved in the development of at least some human leukaemias (Sugimoto et al, 1997). The FHIT transcript lacking exon 3 to 6 was present in 14 of 14 AML, 11 of 13 CML, 5 of 5 ALL and 3 of 5 chronic lymphocytic leukaemia, but in only 1 of 25 normal control samples.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Decreased or altered expression of the FHIT gene has been reported in fresh leukaemia samples and cell lines (Lin et al, 1997;Sugimoto et al, 1997), and loss of normal FHIT function is considered to be involved in the development of at least some human leukaemias (Sugimoto et al, 1997). The FHIT transcript lacking exon 3 to 6 was present in 14 of 14 AML, 11 of 13 CML, 5 of 5 ALL and 3 of 5 chronic lymphocytic leukaemia, but in only 1 of 25 normal control samples.…”
Section: Discussionmentioning
confidence: 98%
“…This was proposed as specific and frequent changes in leukaemia samples. Lin et al (1997) found that 27% AML patients showed the aberrant transcripts and most of them lacked exons 4 to 6. With the subcloning technique, we In the present study, we found that the frequency of loss of normal FHIT expression (pattern III or IV) varied in each type of leukaemia cell line.…”
Section: Discussionmentioning
confidence: 99%
“…For example, aberrant FHIT transcription has been reported in acute myeloid leukemia and ALL. 36,37 The FHIT protein has been implicated as a tumor suppressor gene, but the exact biologic function is not known. 38,39 FHIT was 1 of only 4 discriminating purine pathway genes expressed at a higher level in ALL with the TEL-AML1 fusion.…”
Section: Discussionmentioning
confidence: 99%
“…6 In hematological malignancies, aberrant FHIT transcripts have been reported in acute and chronic leukemia, although it was demonstrated that those aberrant transcripts were observed in both normal and malignant hematopoietic cells. [7][8][9][10] In contrast, the loss or reduced expression of FHIT protein was restricted to malignant hematopoietic cells, while neither loss nor reduction was associated with progression, response to therapy or prognosis in chronic myeloid leukemia (CML) and prognosis in acute lymphocytic leukemia (ALL). 11,12 These results indicated that inactivating alterations of the FHIT gene, which result in the loss or reduced expression of its product, may be involved in the pathogenesis of hematological malignancies, but the clinical significance was not well documented.…”
Section: Introductionmentioning
confidence: 99%